Abordagem Leader: uma aproximação com o programa territórios da cidadania - Rodrigues, Suelen de Leal; Ferreira, Darlene Aparecida de Oliveira [UNESP] (My University, 2014)
Analyzing evidences of the LEADER approach in the Territories of Citizenship Program consists in the immediate objective of this paper. Considering the current context in which the territorial approach takes on the challenge of promoting a less excluding development, the deepening of discussions and experiences highlighted in national and international scope can add elements for analysis and creation of proposals for a more efficient development. Methodologically, a qualitative analysis of bibliographic data and interviews involving focal subject types was performed. In the analysis performed it was possible to understand that the policy of territorial approach is necessary, but it has structural implications that hinder the work of those who should mediate and sensitize the most excluded social groups. Therefore, so that there is an effective policy it would be necessary to create participatory and emancipatory models able to produce structural changes.

Analisar evidencias da abordagem LEADER no Programa Territórios da Cidadania consiste no objetivo imediato do presente texto. Considerando o atual contexto em que a abordagem territorial assume o desafio de promover um desenvolvimento menos excludente, o aprofundamento de discussões e de experiências evidenciadas em âmbito nacional e internacional pode agregar elementos para análise e construção de propostas de desenvolvimento mais eficientes. Metodologicamente foi realizada uma análise qualitativa, de dados bibliográficos, documental e entrevistas focais envolvendo sujeitos tipos. Na análise realizada foi possível constatar que a política de abordagem territorial é necessária, mas possui implicativos estruturais que dificultam o trabalho das instâncias que deveriam mediar e sensibilizar os grupos sociais mais excluídos. Portanto, para que haja uma política eficiente seria necessá- rio criar institucionalidades participativas e emancipadoras que produzam mudanças estruturais.
Leader approach: a closer relationship with theterritories of citizenship program
Keywords: LEADER; Territories of Citizenship; Development; Territory; LEADER; Territórios da Cidadania; Desenvolvimento; Território